Enhancing Students’ Critical Thinking Character Through Case-Based Learning With Online News - Nova, Muhamad; Chaerunnisah, Indah Utami (Jurnal Pendidikan Karakter, 2025)
Critical thinking is not only cognitive skill, but also a character trait, which is a combination of an attitude of curiosity, open-mindedness, systematicity, analyticity, truth-seeking, critical thinking self-confidence, and maturity. Higher educations are required to hone students’ character in learning better and having positive behaviour. This study aimed at identifying the critical thinking character building through the implementation of case-based learning with online news. This study applied qualitative research with a case study design. Conducted at Politeknik Negeri Bali, the study took 27 students and one lecturer as the participants. The data were collected through observation, documentation, and interview and were then analysed by data collection, data reduction, data display, and conclusion drawing. This study revealed that case-based learning with online news could develop the critical thinking character trait through seven stages, including linking, obtaining information, gathering idea, synthesizing, exhibiting, learning, dan feedback collecting. This implementation has reinforced reinforce seven behaviours related to the critical thinking character trait among students, including analytical, curiosity, critical thinking, open-mindedness, truth-seeking, self-confidence, and maturity. Positive feedbacks were also given by the students toward the process of learning with online news, including the raise of sense of awareness, empathy, respectful, and open-minded.